Wide phenotypic diversity for resistance to Phytophthora infestans found in potato landraces from Peru - Pérez, W.; Nahui, M.; Ellis, David; Forbes, G. (Scientific Societies, 2014)
The wild and cultivated species of potato have been utilized in potato breeding to good effect but only a very small sample of the available biodiversity has been exploited. In total, 468 accessions of wild and cultivated species of potato were assessed for resistance to the oomycete pathogen Phytophthora infestans using greenhouse assays. Wide phenotypic variation for resistance was found within a species (i.e., among accessions) but not among species which, on average, were similar. Nineteen accessions had resistance levels better than or similar to the variety Chucmarina, which is routinely used by the International Potato Center as a resistant control. Surprisingly, a number of accessions were significantly more susceptible than the susceptible control, Tomasa Condemayta. Frequency histograms of species indicated continuous variation for resistance with little evidence for functional resistance genes.